Perubahan Tingkat Harga dan Produksi Kelapa Sawit di Wilayah Basis terhadap Kinerja Perdagangan Kelapa Sawit Indonesia - Adi Putra; Wella Sandria (Universitas Batanghari, 2022)
The agricultural sector, especially the plantation sub-sector, has an important role in the national economy, so this sector must receive the government's attention, especially those related to the management and strategic use of its products, which involve the provision of export products to state revenues. This study uses time series data obtained from the Ministry of Agriculture, Central Statistics Agency (BPS), with analytical methods through quantitative descriptive analysis, trend analysis and path analysis. The results showed that the price level and production of palm oil in the Sentra area of Riau, North Sumatra and Central Kalimantan Provinces were still fluctuating, the price level of Palm Oil also affected the production and trade performance of Indonesian palm oil directly or indirectly in the base area. For this reason, the government must respond to barriers to Indonesian palm oil exports, especially those related to competitive trade policies between countries as well as maintaining price stability and national palm oil production.